Gestión logística del Bazar 3 Hermanos de la ciudad de Babahoyo periodo 2022. - Oñate Martínez, Dennise Yolanda (2023)
The administrative management of Bazar 3 Hermanos focuses on the proper handling of resources and coordination of activities to achieve business objectives. Administrative management functions include planning, organization, direction, and control of daily bazaar operations. In terms of planning, long and short-term goals for the bazaar are defined, necessary resources are established to achieve these goals, and responsibilities are assigned to different departments and employees to ensure business success. Organization refers to the bazaar's structure and how human and material resources are assigned to achieve the goals defined in planning. Bazaar administrative management is also responsible for establishing internal policies and procedures, as well as coordinating and supervising employee work. Finally, control refers to the supervision and evaluation of daily bazaar operations to ensure that established objectives and goals are being met. Bazaar administrative management is also responsible for making adjustments and changes to the plan if necessary to improve business performance.